STUDI EFEKTIFITAS SAMBILOTO (ANDROGRAPHIS PANICULATA NEES) UNTUK MENCEGAH PENYAKIT EDWARDSIELLOSIS PADA IKAN PATIN (PANGASIUS HYPOPTHALMUS) - Isje Lukistyowati (Berkala Perikanan Terubuk, 2012)
The aim of the research was to discover the effectiveness of sambiloto(Andrographis paniculata Nees) to prevent Edwardsiellosis infection caused byEdwardsiella tarda in catfish (Pangasius hypopthalmus). Antibacterial activitytest has been carried out from sambiloto solution on E. Tarda using disc diffusionmethod. The concentration sambiloto solution use were 0, 1g/l, 2g/l, 3g/l and 4g/l.This research show that sambiloto solution 5g/l forming the largest clear zoneaverage 9,3 mm. The LD50 test of sambiloto solution given by immersion for 24 hat catfish can harm fish survival when given at doses above 7,30 g / l.Treatment applied was the different dosage of sambiloto by immersion tenminutes give for 30 days. Each fish was immersion with 1 g/l sambiloto (P1), 2 g/lsambiloto (P2) and 4 g/l sambiloto (P3). The fish was feed adlibitum withcommercial fish feed pellets. Before 30 days treatment the fish wereintramuscularly infected with E. Tarda with density of 10 7 cell/ml in a dose of 0,1ml/fish.The best result was obtained in fish after challenged with E.tarda show asignificantly between treatment in P3 (4g/l) (P ˂ 0.05), as the survival rate was100 % and non-specific defence in the catfish show hematocrite level is 22,67 %,total leucocytes is 31,70 thousand cell/mm3 and the percentage of phagocytoticactivity at 55,5 %.Keywords: Catfish, Andrographis paniculata , antimicrobial, Edwardsiella tarda